(untitled) (Bulletin of criminological association of Ukraine, 2023)
The article emphasizes that the criminalistics description allows for the identification of specifics in the mechanism of committing corruption crimes associated with receiving illicit benefits, which is later considered during the planning, organization, and execution of investigations into specific crimes of the outlined category. It is highlighted that the content of the criminalistics description must be regularly reviewed, as the mechanisms of corruption crimes in general, and those involving illicit benefits in particular, continuously evolve under the influence of changes in the criminogenic environment, legislative reforms in the relevant sphere of social relations, informatization, and digitalization of all spheres of human activity, including criminal activity. It is proposed to define the criminalistics description of corruption crimes associated with receiving illicit benefits as a theoretical category formed based on the analysis of empirical data on the mechanism of committing the investigated category of crimes, presented in the form of an informational model that allows for the selection of optimal means and methods for investigating crimes. Considering the established scientific approaches to structuring the criminalistics description of corruption and related criminal offenses, as well as generalized empirical data on the patterns of mechanisms of committing corruption crimes associated with receiving illicit benefits, the following elements of the criminalistics description of the investigated category of crimes have been identified: the personality of the offender and the victim; typical methods; the subject and the trace pattern.